Government Policy on Blending Ethanol into Pertamina's Fuel: Implications and Challenges - Nurita, Riski Febria; Nahuddin, Yusuf Eko (International Journal of Sustainable Law, 2025)
The Indonesian government has embraced renewable energy policies as part of its commitment to reducing reliance on fossil fuels and mitigating the effects of climate change. Among these policies is the integration of ethanol into the nation's fuel supply, specifically through blending with Pertamina's fuel. This study investigates the implications and challenges of Indonesia's ethanol blending policy, with a focus on its legal, economic, and environmental dimensions. The research adopts a normative legal methodology, examining existing laws, regulations, and policies related to biofuels and ethanol blending, as well as analyzing key stakeholders' roles in implementing the policy. Through the review of legal documents, interviews with experts, and relevant case studies, the study highlights the benefits of ethanol blending in terms of energy security and environmental sustainability, while also discussing the barriers to its full implementation. The findings suggest that while ethanol blending holds potential for reducing carbon emissions and supporting the local biofuel industry, the policy faces challenges such as infrastructure readiness, cost-effectiveness, and market acceptance. The study concludes with recommendations for enhancing the policy's effectiveness and its alignment with Indonesia's broader renewable energy goals.